COMPARATIVE STUDY ON READING COMPREHENSION BETWEEN STUDENTS OF JUNIOR HIGH SCHOOLS IN CITY AND RURAL AREA - Lilis - Sholihah (Premise: Journal of English Education and Applied Linguistics, 2013)
This study is aimed to: (1) find out the differences on reading comprehension between students of junior high school in city and rural area, (2) to find out factors that causes differences on reading comprehension between students in city and rural area. This resarch was carried out in SMPN 1 Serang, SMPN 1 Cilegon, SMPN 1 Picung and SMPN 1 Banjarsari. The method used was quantitative method in the form of comparative study. The writer used Ex Post Facto Design in this research. The population of the research was all the third year students of those four schools. The sampling technique was purposive sampling. The writer took 80 students for the sample. The instruments for collecting data were questionnaire, interview, test and also unstructured observation. The technique used to analyze data was T-Test separated variance and polled variance. The result of the study showed that there was a significant difference of students reading comprehension between students in city and rural area. It can be seen from the result of the test. Based on questionnaire which were given to the students and interview for the teacher, the researcher could find out the factors that cause differences on reading comprehension between students in city and rural area, such as the students’ interest, motivation of students, teaching methodology, reading material, vocabulary mastery, and culture.